From Methodology to Post-Methodology: Teacher Education in Syria - Al-Issa, Ahmad (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
To teach is to teach creatively not to be servile to any methods no matter how powerful they might be. Nobody knows the students more than their own teachers. Nobody knows their needs, interests, desires and background more than their own teachers. More importantly, nobody knows the students’pedagogical problems and the suitable solutions more than the teachers themselves. A priori approaches aggravate the already declining teaching situation. Non-customized methodology suffocates the spirit of teaching. It undermines the learners’ centeredness and the teachers’ creativity. The one-size-for-all-approach is against the grain of teaching. The same textbook, the same lessons, the same techniques, the same examsand the same assessment are a recipe for cloning not for teaching. To teach is to personalize and to customize. The universal must be localized. The general must be specified. The collective must be individualized and the canon must be de-standardized. What is not relevant must be made relevant. The hauntology of methodology is over. This is the age of post-methodology.